ENDING SLAVERY IN THE CORPORATE SUPPLY CHAIN storytelling, leadership, and the coalition of... immokalee workers. - Herder, Richard ([S.l.] : ROUTLEDGE, 2024)
The Coalition of Immokalee Workers (CIW) is a Florida-based farmworkers' cooperative that has received international acclaim for sponsoring anti-slavery investigations. In 2011, they worked with commercial tomato growers to found the Fair Food Program, a private sector agreement that operates according to the principles of worker-driven social responsibility (WSR). Researchers have lauded WSR as an alternative to traditional corporate social responsibility (CSR) programs, which have failed to curb human exploitation in global markets. The Fair Food Program has been credited with ending slavery and other human rights abuses in Florida's tomato industry and is now expanding to other sectors of the food economy in the United States and several other nations. Researchers have called for WSR programs to be included in a smart mix of public and private initiatives aimed at abolishing slavery and other types of exploitation in global supply chains. The book introduces a theory of ensemble storytelling to explain how the CIW has been able to animate workers, fight slavery, influence multinational corporations, and expand the Fair Food Program. The phrase ensemble storytelling refers to a set of collective, dynamic storytelling practices. They are described as foundational to the operation of any WSR program.
Keywords: Coalition of Immokalee Workers; Social responsibility of business; Antislavery movements; International trade -- Moral and ethical aspects; Agricultural laborers -- Labor unions -- Florida -- Immokalee; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Labor